HALAL SLAUGHTERHOUSE TO ACHIEVE HALAL VALUE CHAIN OF THE RESTAURANT AND MEAT-PROCESSED FOOD INDUSTRY - Pratiwi, Heni; Ambiya, Qorry; Mahfudhoh, Azizatul; Saputra, Muhammad Nanda (Proceeding International Seminar of Islamic Studies, 2023)
Indonesia is the 4th most populous country in the G-20 with 86.9% of population being Muslim. The Muslim population growth is increasing every year. In Indonesia, Halal product guarantees regulated in Law No. 33 of 2014 classify slaughter services as the third group that must be halal certified in October 2024. The results of our research found that the obligation of halal certification for the first group is on food and beverage products and the second group, raw materials, food additives and auxiliary materials for food and beverage products are also heavily influenced by slaughter services, particularly for processed meat products.Slaughterhouses (RPH) that already have halal certification will facilitate certification for restaurants and processed meat businesses, thus halal certification in slaughterhouses (RPH) will be sustainable to achieve halal value chain of the restaurant and meat-processed food industry. This study aims to answer the problems of slaughterhouses (RPH) in Indonesia in terms of halal certification and the impact of fulfilling halal slaughterhouses (RPH) for sustainable halal certification. In this study, the authors used a qualitative descriptive approach with observation techniques and literature studies.